PERANAN KEMASAN (PACKAGING) DALAM MENINGKATKAN PENJUALAN PRODUK UMKM DI BINTAN BUYU - Sambodo, Bambang; Chairunnisa, Afifah; Sarabiti, Anil Kumar; Aulia, Hendiaz; Windira, Novi Ayu; Puspita, Try Surya (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2025)
This research aims to increase product marketing and sales by selecting safe and durable packaging. This research is a type of qualitative research to explain the contribution of packaging to Micro, Small and Medium Enterprises. The method of data analysis is the process of searching for and compiling data obtained through interviews, field notes and documentation in a systematic way. By using this research we were able to dig up various information about Ms. Marini's Spicy Sweet Potato Chips and Ms. Surya's Peanut Cake. The existence of packaging is needed by Micro, Small and Medium Enterprises (MSMEs), which incidentally still use non-standard packaging